1996
DOI: 10.1046/j.1365-3024.1996.d01-52.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro stimulation of naive mouse lymphocytes by Heligmosomoides polygyrus adult worm antigens induces the production of IgG1

Abstract: The production of high levels of IgG1, by mice chronically infected with the parasitic nematode Heligmosomoides polygyrus, has been documented for a number of years. In order to investigate this phenomenon, naive lymphocytes from B10.D2 mice were incubated in vitro with H. polygyrus adult worm homogenate (AWH) and the culture supernatants examined for immunoglobulin production. Stimulation of pooled naive splenocytes by AWH was found to produce IgG1, but not IgM, in an antigen dose dependent manner. Identical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…For example, the nematode Heligmosomoides polygyrus contains immunomodulatory factors capable of either stimulating (1,2) or inhibiting (3,4) T and B cell responses. With respect to Ascaris suum, we and others have shown that infection with the nematode or the use of its soluble products or extracts at different stages of purification potentiates or suppresses the immune responses (5)(6)(7).…”
mentioning
confidence: 99%
“…For example, the nematode Heligmosomoides polygyrus contains immunomodulatory factors capable of either stimulating (1,2) or inhibiting (3,4) T and B cell responses. With respect to Ascaris suum, we and others have shown that infection with the nematode or the use of its soluble products or extracts at different stages of purification potentiates or suppresses the immune responses (5)(6)(7).…”
mentioning
confidence: 99%
“…An extract of the intestinal nematode parasite Heligmosomoides polygyrus has recently been reported to stimulate the production of IgG1 in naive spleen cell culture in vitro (56). The data in that study showed that the extract mediated its effect by stimulating T cells to produce a factor (presumably IL-4) that induced IgG1 production in the culture.…”
Section: Discussionmentioning
confidence: 94%
“…It is important to note that both the immune response to nematodes and the modulation of that immune response by nematode factors are likely to be very complex. For example, Price and Turner (33) have shown that a somatic extract of Heligmosomoides polygyrus inhibits B-cell proliferation but, in contrast, Robinson and coworkers (38) reported that a similar extract stimulated IgG1 production in vitro. Moreover, extracts from A. suum have been reported to stimulate (20) and to inhibit (13, 39) B-cell function.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in contrast to the immunostimulatory activity of the body fluid of Ascaris reported above, Ferreira and coworkers (13) and Soares and coworkers (39, 40) have reported immunomodulatory factors in secretions of A. suum, which ablate B-cell responses. Similarly, the nematode Heligmosomoides polygyrus has been reported to contain immunomodulatory factors capable of either stimulating (37,38) The prevailing evidence supports a significant role for accessory cells in the activation of T and B cells both in vivo and in vitro (7, 41). This has prompted numerous investigations into the role of macrophages in helminth-mediated immunomodulation of lymphocyte function (2,15,17,22,27,28,36).…”
mentioning
confidence: 99%
See 1 more Smart Citation